On KLT and SYM-supergravity relations from 5-point 1-loop amplitudes - Nastase, Horatiu [UNESP]; Schnitzer, Howard J. (Springer, 2011)
We derive a new non-singular tree-level KLT relation for the n = 5-point amplitudes, with manifest 2(n-2)! symmetry, using information from one-loop amplitudes and IR divergences, and speculate how one might extend it to higher n-point functions. We show that the subleading-color N = 4 SYM 5-point amplitude has leading IR divergence of 1/epsilon, which is essential for the applications of this paper. We also propose a relation between the subleading-color N = 4 SYM and N = 8 supergravity 1-loop 5-point amplitudes, valid for the IR divergences and possibly for the whole amplitudes, using techniques similar to those used in our derivation of the new KLT relation.
Keywords: Supersymmetric gauge theory; Extended Supersymmetry; 1/N Expansion; Supergravity Models